STRENGTH PROPERTIES OF CEMENT STABILIZED CLAY SOIL WITH EPS FOOD PACK WASTE - Dauda, Auwal; Yunusa, G. H. (FUDMA Journal of Sciences, 2024)
The purpose of this study is to investigate the impact of EPS on geotechnical properties of soil through laboratory test and ANOVA analysis. These tests have been conducted on natural and stabilized soils in accordance with procedure outlined in BS1377 (1990). Four fibre contents (0.25%, 0.5%, 0.75%, and 1%) of the dry soil weight and three fibre size (random size, 20 mm x 2mm size and 20 mm x 5 mm) were used. The tests conducted included particle distribution, specific gravity, Atterberg limits, the standard compaction, California Bearing Ratio (CBR), Unconfined Compressive Strength (UCS). The laboratory result classifies the soil as A-7-6 (17) according to American Association of States Highway and Transport Officials (AASHTO) classification system and Clay soil of Low plasticity (CL) in accordance with the Unified Soil Classification System (USCS). The Specific gravity decreases from 2.7 to 2.1. MDD results also shows a decrease with increase of EPS waste fibre from 1.46Mg/m3 to 1.32Mg/m3 for British Light compaction and from 1.61Mg/m3 to 1.47Mg/m3 for British Heavy. The CBR result shows an improvement from 5.33% to a maximum value of 10.5% at 1% EPS waste fibre for unsoaked CBR and from 2.86% to a maximum of 7.73% at 0.5% EPS waste fibre for soaked CBR. The UCS result shows an improvement at 28 days from 2410 kN/m2 of Natural soil to a maximum of 5593kN/m2 at 0.5% EPS waste fibre. Based on the laboratory experimental result it was suggested that the EPS waste fibre of 0.5% dosage can be...
Keywords: Cement; Expanded polystyrene food pack waste; Clay soil; Califonia bearing ratio; Unconfined compressive strength